Universitetet i Agders røtter er 175 år i 2014 – Andreas Faye og Holt seminar - Jahr, Ernst Håkon (Scripta Neophilologica Posnaniensia, 2018)
The University of Agder changed status from a university college to a full-fledged university with all university privileges in 2007. However, the academic roots of the university go back to the year 1839, when the first teacher training college was established in Holt in Agder, close to the small town of Tvedestrand. This year (2014), then, the University of Agder can celebrate that the oldest studies at the university are 175 years old. This paper takes a closer look at the man who became the first rector of the college at Holt, the priest Andreas Faye (1802-69). Faye was an extremely active scholar and an important pioneer in several areas – folklore, history and education being perhaps the most important ones. This paper also shows how he, and more than his contemporary Norwegian colleagues, was engaged in an international network of researchers, especially in Denmark and Germany.